Long time existence for the quadratic wave equation associated to the harmonic oscillator. (January 2016) - Zhang, Qidi
Abstract: We show the solution for the quadratic wave equation associated to the harmonic oscillator exists over a longer time interval than the one given by local existence theory. The key point is that the nonlinearity is quadratic so that we can estimate the small divisor and perform a normal form process.